Eight times the difference of y and nine

Answers

Answer 1
Answer:

Eight times the difference of y and nine will be 8(y - 9).

It should be noted that eight times the difference of y and nine simply means that one has to subtract 9 from y and then multiply the difference by 8.

Therefore, eight times the difference of y and nine will be 8(y - 9).

In conclusion, the correct option is 8(y - 9).

Read related link on:

brainly.com/question/16081696

Answer 2
Answer:

Answer:

(y-9)8

Step-by-step explanation:

you first solve 8-9, and then multiply is by 8.


Related Questions

There are 3 bags each containing 100 marbles. Bag 1 has 75 red and 25 blue marbles. Bag 2 has 60 red and 40 blue marbles. Bag 3 has 45 red and 55 blue marbles. Now a bag is chosen at random and a marble is also picked at random. 1) What is the probability that the marble is blue? 2) What is the probability that the marble is blue when the first bag is chosen with probability 0.5 and other bags with equal probability each? Make sure to clearly define your probabilistic events and mathematically show how different probability laws and rules that you learned in class could be applied to solve the problems.
I NEED AN EXPLANATION PLEASE!! I need a fast answer
Evaluate.19+(22 - 16) =
33 + 2(5+8) - (6-2)2 =
Bo and Erica are yoga instructors. Between the two of them, they teach 44 yoga classes each week. If Erica teaches 13 fewer than twice as many as Bo, how many classes does each instructor teach per week?A. 23 Bo; 21 EricaB. 21 Bo; 23 EricaC. 16 Bo; 28 EricaD. 19 Bo; 25 Erica

Find the seventh term of thegeometric sequence, given the
first term and common ratio.
a_=1 and r=-2/3
[?]

Answers

Answer:

T_7 = (64)/(729)

Step-by-step explanation:

Given

a =1

r = (2)/(3)

Required

Determine the 7th term

The nth term of a gp is:

T_n = a * r^{n-1

So, we have:

T_7 = 1 * (2)/(3)^{7-1

T_7 = 1 * (2)/(3)^{6

T_7 = 1 * (2^6)/(3^6)

T_7 = 1 * (64)/(729)

T_7 = (64)/(729)

Recall that a test is statistically significant at a particular significance level if the null hypothesis is rejected when alpha is set at this value. Suppose a medical researcher conducts a statistical test of hypotheses and finds there is statistically significant evidence for the alternative hypothesis at a significance level alpha = 0.05. The researcher may conclude that...a) the test would also be statistically significant at level alpha = 0.01b) the test would also be statistically significant at level alpha = 0.10c) both of the above are trued) none of the above are true

Answers

Answer:

The correct option is: b) the test would also be statistically significant at level alpha = 0.10

Step-by-step explanation:

Consider the provided information.

Suppose a medical researcher conducts a statistical test of hypotheses and finds there is statistically significant evidence for the alternative hypothesis at a significance level alpha = 0.05.

It means that the test would be statically significant at level alpha = 0.10

As we know that if alternative hypothesis is true then the value of p must be less than α.

That means if the p-value is less than 0.05 then it must be less than 0.10.

Hence, the correct option is: b) the test would also be statistically significant at level alpha = 0.10

Can I use this for my homework for science because am a little girl trying to get an A+ I hope you understand cuz I want a free college I have money but I don't want to waste my moneeeeeyyyyy

Answers

yes of course, college fees are hard, just make sure you try te questions by yourself first, before you go to this, otherwise you are making no effort, and that may hurt you later in life. but yes, you can use this site, i understand why you want to do that.

Identify the like terms in this expression: 3xy + 2x-7xy+4x2

Answers

Answer:

3xy and -7xy, 2x and 4x

Step-by-step explanation:

3xy and -7xy these are the only 2 like terms in this expression

Use induction to prove the following formula is true for all integers n where n greaterthanorequalto 1. 1 + 4 + 9 + .. + n^2 = n(n + 1)(2n + 1)/6

Answers

Answer with Step-by-step explanation:

Since we have given that

1+4+9+........................+n² = (n(n+1)(2n+1))/(6)

We will show it using induction on n:

Let n = 1

L.H.S. :1 = R.H.S. : (1* 2* 3)/(6)=(6)/(6)=1

So, P(n) is true for n = 1

Now, we suppose that P(n) is true for n = k.

1+4+9+...................+k^2=(k(k+1)(2k+1))/(6)

Now, we will show that P(n) is true for n = k+1.

So, it L.H.S. becomes,

1+4+9+......................+(k+1)^2

and R.H.S. becomes,

((k+1)(k+2)(2k+3))/(6)

Consider, L.H.S.,

1+4+9+..+k^2+(k+1)^2\n\n=(k(k+1)(2k+1))/(6)+(k+1)^2\n\n=k+1[(k(2k+1))/(6)+(k+1)]\n\n=(k+1)[(2k^2+k+6k+6)/(6)]\n\n=(k+1)(2k^2+7k+6)/(6)]\n\n=(k+1)(2k^2+4k+3k+6)/(6)]\n\n=(k+1)[(2k(k+2)+3(k+2))/(6)]\n\n=((k+1)(2k+3)(k+2))/(6)

So, L.H.S. = R.H.S.

Hence, P(n) is true for all integers n.

PLEASE HELP

How do I solve 7,9, and 10 also what are the answers?

Answers

7.
360 degrees- the other angles = x